Dinâmica de formação e manutenção de parcerias sob à ótica da teoria dos curstos de transação: um estudo de caso no setor de mineração - Charles Galvani Portes (2007)
The new global scene, mainly characterized for the strong competition in all the sectors of the economy, has built an environment of great turbulence for the organizations, which instead of being isolated systems, desire, each time more, to deal with all the agents of the productivechain focusing on the most profitable niches of the market. Consequently, they face the necessity of reevaluating their strategies of formation and maintenance of partnerships, with the objective of better results. These relations can be presented as long term partnerships, alliances, outsourcing, relations with written contracts, among others. In this context, the Transaction Costs Theory appears as a support to the decision for managers of diverse areas. This theory defends the existence of the Transaction Costs, costs these that appear from theaccomplishment of any type of partnership. From a case study in the field of operations, this work evaluated the process of a relation between supplier and purchaser, with the objective to evaluate the stages of formation and maintenance of this relationship. Despite the partnershiphas been constructed without the aid of the Transaction Costs Theory as analysis support, it could be noticed a great similarity of concepts and objectives between the organizations. On the other hand, related critical points have been observed, referable to the limited rationality and the asymmetry of information. In the end of the work it has been concluded that the usage of the Transaction Costs Theory could have brought a more comfortable and transparent environment between the involved ones, avoiding some efforts and occurred consuming, generating a more effective result.